Aspirin Slow Release Tablet Formulation With Comparison Of HPMC And Pectin As Matrix - Lestari, Kurni Ambar; Nawangsari, Desy; Sunarti, Sunarti (Pena Medika : Jurnal Kesehatan, 2023)
Aspirin is an antiplatelet drug that is used in the elderly as stroke therapy, while in elderly patients compliance with taking the drug often decreases. The aim was to determine the physical properties, dissolution, and stability of aspirin slow-release tablets with a comparison of HPMC and pectin as the matrix. Aspirin slow-release tablets were made in 3 formulas with HPMC and pectin ratios of 15%:10%, 12.5%:12.5%, and 10%:15%. Evaluation of slow-release tablets includes weight uniformity, size uniformity, hardness, friability, floating time, and dissolution tests. The data obtained was then analyzed using a one-way ANOVA. The results showed that in the physical properties test of the tablet, the results were F1, 2 and 3, including the weight uniformity test, the ANOVA results were 0.000<0.05, the size uniformity test was 0.055>0.05 in diameter and the thickness was 0.899>0.05, the hardness test was 0.355> 0.05, fragility test 0.780>0.05 and float time test at lag time F1 48 ± 3, F2 49 ± 4.35, F3 50 ± 1.52 at the duration time the results were 8 hours and in the F1 dissolution test 9, 20%, F2 10.14% and F3 8.14%. In physical stability, the results obtained were uniform tablet weight, uniform size, stable tablet hardness, stable tablet friability, and a stable floating time test, while in chemical stability, there was a change in the dissolution percentage, with the results on the 14th day of F1 stability being 11.79%. ,F2 11.05%, and F3 9.22%, and on the 28th day of stability, F1 10.55%, F2 10.51%, and F3 10.46%. Results that have significant differences (p<0.05) include weight uniformity (p=0.000)